Induction of a fibrogenic response in mouse colon by overexpression of monocyte chemoattractant protein 1. Issue 5 (18th November 2005) - Motomura, Y; Khan, W I; El-Sharkawy, R T; Verma-Gandhu, M; Verdu, E F; Gauldie, J; Collins, S M
Abstract : Background and aims: Monocyte chemoattractant protein 1 (MCP-1) is increased transmurally in inflammatory bowel disease (IBD). Although MCP-1 is considered to play an important role in fibrotic disease in other organs, the role of MCP-1 in gut fibrosis is unknown. We investigated the fibrotic potential of MCP-1 in the gut by overexpressing this chemokine in the mouse colorectal wall. Methods: Intramural gene transfer by direct injection of adenovector into the mouse rectal wall was established. C57BL/6 and Rag2 −/− (B and T cell deficient) mice received 2.5×10 9 plaque forming units of an adenovector encoding murine MCP-1 (AdMCP-1) or control virus (AdDL70) via intramural injection. Mice were killed at various time points and tissues were obtained for histopathological and biochemical analysis. Results: AdMCP-1 significantly increased collagen production in the colorectum and this was associated with significant elevation of transforming growth factor β (TGF-β) and tissue inhibitor of metalloproteinase (TIMP-1) protein. Transmural collagen deposition was observed after AdMCP-1 administration, and was accompanied by CD3+ T cells, F4/80+ macrophages, and vimentin+ cell infiltrates. Collagen was differentially distributed, with type I deposited in the muscularis mucosa and muscularis propria and type III in the submucosa and myenteric plexus. AdMCP-1 failed to induce collagen overproduction in immunodeficient Rag2 −/− mice. Conclusion: These findings suggest that MCP-1 can induce fibrosis in the gut and that this process involves interaction between T cells and vimentin positive fibroblasts/myofibroblasts, as well as the subsequent upregulation of TGF-β and TIMP-1 production. This model provides a basis for considering MCP-1 in the pathogenesis of strictures in IBD.